SILFA Model Approach Development for Women Artisans’ Education and Empowerment: Integrating Karawo Cultural Heritage into Non-Formal Learning - Silfana Abdul; Abd Hamid Isa; Mohamad Zubaidi; Misran Rahman; Sri Nurhayati; Gumpanat Boriboon; Udeme Samuel Jacob (IJECA (International Journal of Education and Curriculum Application), 2025)
Women artisans in rural areas face persistent barriers in accessing education and achieving economic empowerment, particularly when their livelihoods rely on sustaining fragile cultural heritage traditions. This study developed and piloted the SILFA Model Approach for Women Artisans’ Education and Empowerment, integrating Karawo cultural heritage into non-formal learning. The model aims to provide a culturally grounded learning framework that enhances skills, knowledge, and socio-economic agency while preserving heritage identity. Employing a Research and Development design guided by the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation), the research involved thirty women artisans in Pongongaila Village, Gorontalo, Indonesia, with ten participating in a small-group pilot implementation. Quantitative data from pre- and post-tests were analyzed using descriptive statistics, while qualitative data from focus group discussions, reflections, and observations were interpreted through thematic analysis. Results showed a substantial improvement in knowledge and skills, with mean scores increasing from 47.4 to 80.4. Participants also reported heightened confidence, creativity in developing new Karawo motifs, adoption of digital marketing, and motivation to establish cooperative groups. Conceptually, the SILFA Model contributes to theories of women’s empowerment and culture-based education by operationalizing sustainability, interactivity, and identity-preserving principles within a participatory non-formal learning context. As a validated pilot framework, it demonstrates how embedding cultural heritage in non-formal education can simultaneously revitalize Karawo traditions and strengthen women’s educational and economic empowerment in rural communities.